Design and Mathematical Modelling of Solar Powered Cardiac Pacemaker - Ailiya Munawar; M.Ismael; Arsalan Ansari (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Least physical activity and unhealthy lifestyle resulted in increased cardiac issues in past decade but the advancements in bioengineering addressed the cause by introducing photo-voltaic cells in medical industry. Hence, the battery less pacemakers evolved making the pacemakers cost effective (no battery replacement after ten years). In this paper a comprehensive mathematical modelling of a system including Heart beat block, the sensor block, the pace maker block and the circulatory system block is done. And their outputs on scope is analyzed for adjusting the parameters of mathematically equations designed with generalized equations. The resulting waveform of the system is then compared to the standard QRS wave of a human heart’s ECG. Our proposed cardiac solar pacemaker, uses solar power as source for charging the battery of pacemaker, hence eliminating the procedure of battery replacement and re-surgery after five to ten years. We started the mathematical modelling by deriving transfer functions of the blocks designed in Simulink, evaluating the characteristic equations in Laplace domain and frequency domains. The constants of transfer functions are retrieved via mathematical techniques and then the resulting system response is analyzed by the fractional analysis of the transfer functions